Kegiatan Perlombaan Keagamaan bagi Anak-Anak: Upaya Meningkatkan Kepercayaan Diri Siswa Mengikuti Perlombaan - Purbatua Manurung; Khofifah Tanjung; Marini Kurniati; Masdura Siregar; Maslan Maslan; Lu’lu’ Ul Jannah (El-Mujtama: Jurnal Pengabdian Masyarakat, 2023)
One of the factors that influence a child's self-confidence is a less supportive environment. Based on what happened in the competition, there were some children who were not confident when participating in religious competitions. In addition, the absence of skills possessed by a child is one of the factors that cause a child to not be confident. For this reason, the need for motivation from parents and support from the environment is very important for children as an effort to foster self-confidence in a child. Self-confidence is an attitude or belief that a person has for his abilities. One of the efforts that can be done to foster self-confidence in a child is by conducting group guidance. In this group guidance service, there is a change or effect on the individual himself. Where the self-confidence of students before and after group guidance experienced a difference, namely experiencing a better and more active increase. Keywords: Religious Competition, Confidence